Beyond Anthropocentrism: A Posthumanist Reflection on Artificial Intelligence and Emotion in Klara and the Sun - Tan, Qi; Huang, Yuwei (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
Kazuo Ishiguro’s Klara and the Sun, through the perspective of the artificial intelligence character Klara, deconstructs the traditional anthropocentric ethical framework, delving into the intersections of emotion, ethics, and subjectivity in human-machine relationships. As an artificial intelligence being, Klara’s unique emotional capabilities and interactions with humans challenge humanity’s presumed ethical and subjective superiority, revealing the potential for more equitable relationships in a technologically advanced society. Grounded in posthumanist theory, this study employs close textual analysis and ethical reflection to examine how Klara and the Sun interrogates the limitations of anthropocentrism through Klara’s emotional expressions, ethical choices, and responses to human emotional structures. It argues for a nuanced and diverse ethical framework in future human-machine symbiosis. By exploring the representation of artificial intelligence’s emotional agency, this paper not only demonstrates how technology redefines ethical relationships between human and non-human entities but also highlights AI’s potential to reshape and challenge the future ethical landscape.